2013
DOI: 10.3171/2012.12.spine12607
|View full text |Cite
|
Sign up to set email alerts
|

Fusion rates in multilevel, instrumented anterior cervical fusion for degenerative disease with and without the use of bone morphogenetic protein

Abstract: The overall rate of bony arthrodesis was increased following the use of BMP in multilevel anterior cervical fusion. Traditional methods without BMP had a high rate of pseudarthrosis. The complications associated with the use of BMP appeared to be dose related and of low incidence when BMP is used in doses equal to or less than 1.1 mg/level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…While some studies exist about the effectiveness of growth factor treatment for vertebral body fusion and IVD implants [29-31]; to our knowledge nothing is known about the effect of growth factor injection during discectomy. Our broad aim is to improve knowledge of how discectomy procedures influence IVD physiology and assess the potential of growth factor injection at the time of surgery, and we specifically evaluate the effects of TGFβ3 injection into the discectomy site during surgery using a bovine organ culture model.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies exist about the effectiveness of growth factor treatment for vertebral body fusion and IVD implants [29-31]; to our knowledge nothing is known about the effect of growth factor injection during discectomy. Our broad aim is to improve knowledge of how discectomy procedures influence IVD physiology and assess the potential of growth factor injection at the time of surgery, and we specifically evaluate the effects of TGFβ3 injection into the discectomy site during surgery using a bovine organ culture model.…”
Section: Introductionmentioning
confidence: 99%
“…Is a major limitation of multilevel anterior cervical fusion, traditional techniques have a 20% of patients who develop pseudarthrosis, one strategy used to help decrease the rate of it is to have posterior instrumentation to increase the rigidity of the construct, however it adds morbidity by increase the time of surgery. Frenkel et al 16 demonstrate that BMP usage in anterior cervical approach has almost 100% rate of solid arthrodesis regardless of level, but its study does not have statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Stachniak et al reported a 95 % fusion rate at 6-months and a 100 % fusion rate at 9-months following a 2-or 3-level ACDF with rhBMP-2 in a group with substantial risk factors for pseudarthrosis (33 % smoking, 13 % diabetes, and 43 % obesity) [53]. In another retrospective cohort study comparing multilevel ACF with and without rhBMP-2, the authors demonstrated a 100 % fusion rate in the rhBMP-2 cohort vs an 82.6 % fusion rate in the group without rhBMP-2 [44]. Lastly, Lu et al demonstrated lower rates of pseudarthrosis with the application of BMP in multilevel ACF, especially in patients who underwent a 4-level ACDF and in smokers [56].…”
Section: Arguments In Favor Of Bmp Utilization In the Anterior Cervicmentioning
confidence: 93%
“…Controversy still exists regarding the administration of BMP in ACF. Some groups maintain that it is safe and efficacious [43,44] while others report multiple serious complications [45,46]. Argument against BMP utilization in the anterior cervical spine On July 1, 2008 the FDA issued a public health notification warning about the utilization of rhBMP-2 in cervical spine fusion procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation